Determination of freeze-out conditions from fluctuations in the Hadron Resonance Gas model. (March 2015) - Alba, P; Alberico, W; Bellwied, R; Bluhm, M; Sarti, V Mantovani; Nahrgang, M; Ratti, C
Abstract: Fluctuations of conserved charges measured in Heavy-Ion Collisions (HICs) received increasing attention in recent years, because they are good candidates to explore the phase diagram of QCD matter. During the last year, net-electric charge and net-proton moments of multiplicities measured at RHIC have been published by the STAR collaboration, for a range of collision energies which spans a region of the phase diagram at finite chemical potential. Here we present a new freeze-out curve obtained using the Hadron Resonance Gas (HRG) model approach to fit these experimental data. The HRG model is modified in order to have a realistic description of the HICs: kinematic cuts, resonance feed-down and resonance regeneration are taken into account. Our result is in agreement with preliminary studies by the ALICE collaboration, and is supported by a recent lattice analysis of the same quantities.